ANALISIS FAKTOR YANG MEMPENGARUHI KUALITAS LAPORAN KEUANGAN PEMERINTAHAN DAERAH (Studi Pada Badan Pengelolaan Keuangan dan Aset Daerah di Kabupaten Manokwari) - Anik Wuriasih (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2019)
This study aims to examine the influence of several factors (human resources quality, information technology utilization, internal control systems and organizational commitments) on the quality of the financial information of local government in Manokwari. Type of data uses in this research is primary data which have been obtained from questionnaires which are directly distributed to the respondents who are the head and the staffs of accounting division on financial and asset management services area (BPKAD) of Manokwari. The number of population and study sample was 46 people. Sampling using sampling methods saturated. This research data analysis method is multiple linear regression. Results of this study can be conclude that the human resources quality, internal control systems and organizational commitments have a significant positive effect on the quality of local government financial reporting information, while the use of information technology utilization does not have an effect on the quality of local government financial reporting information. Suggestion for the further research is to expand the independent variables that affect the quality of the financial information of local government.